Firm Value and Financial Performance : Systematic Literature Review (Jurnal Ekonomi Bisnis dan Akuntansi, 2025)
This article aims to conduct a systematic literature review of empirical and theoretical studies of the last five years (2020–2024) that discuss the relationship between financial performance and company value in various countries. The study summarizes the most commonly used financial performance indicators, such as ROA, ROE, EPS, and NPM, and evaluates their contribution to a company's value. In addition, this article analyzes the consistency and variation of research results based on methodology, geographic location, industry type, and theoretical approaches such as signal theory, agency, and stakeholders. The literature selection process is carried out through reputable databases (Scopus, Web of Science, ProQuest) with certain inclusion criteria. The results of the review show that internal factors such as CSR, ESG, green innovation, and risk management generally have a positive effect on the company's performance and value, depending on the context of implementation. This article is expected to be a critical and useful reference for future researchers in developing similar studies.